2010
DOI: 10.1111/j.1476-4431.2010.00523.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous versus intermittent delivery of nutrition via nasoenteric feeding tubes in hospitalized canine and feline patients: 91 patients (2002-2007)

Abstract: PPND was not significantly different for continuous versus intermittent feeding via nasoenteric tubes. Frequencies of gastrointestinal complications were not significantly different between patients fed continuously and patients fed intermittently. Enterally fed dogs had a significantly higher frequency of regurgitation and diarrhea than enterally fed cats. Prospective studies are warranted to investigate causes for these potential inter-species differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 13 publications
2
22
0
1
Order By: Relevance
“…Two veterinary studies published in 2010 investigated the differences between bolus feeding and continuous feeding (Campbell et al, 2010. In a retrospective study there was no difference in the percentage of nutrients delivered over 24 hours (Campbell et al, 2010). Although there was a statistically significant difference in percentage nutrients delivered in a prospective study, the authors commented that this difference would probably not be clinically significant .…”
Section: Feeding Methodsmentioning
confidence: 73%
See 1 more Smart Citation
“…Two veterinary studies published in 2010 investigated the differences between bolus feeding and continuous feeding (Campbell et al, 2010. In a retrospective study there was no difference in the percentage of nutrients delivered over 24 hours (Campbell et al, 2010). Although there was a statistically significant difference in percentage nutrients delivered in a prospective study, the authors commented that this difference would probably not be clinically significant .…”
Section: Feeding Methodsmentioning
confidence: 73%
“…Two veterinary studies published in 2010 investigated the differences between bolus feeding and continuous feeding (Campbell et al, 2010. In a retrospective study there was no difference in the percentage of nutrients delivered over 24 hours (Campbell et al, 2010).…”
Section: Feeding Methodsmentioning
confidence: 99%
“…A study by Klaus and others (2009) demonstrated a that the target calorie provision was reached sooner with constant rate infusion feeding than bolus feeding in cats. More recently however, a study by Campbell and others (2010) comparing intermittent to continuous feeding found no difference in the percentage of nutrients delivered or the rate of complications.…”
Section: Management Of Anorexiamentioning
confidence: 96%
“…A recent study found no difference when administering continuous versus intermittent (bolus) feeding via nasoenteric tubes in the percentage of prescribed nutrition delivered or the frequency of GI complications (Campbell et al . ).…”
Section: Therapeutic Targetsmentioning
confidence: 97%